2021
DOI: 10.3389/fvets.2021.627894
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Development of Bovine Respiratory Disease: A Cross-Sectional Study in Beef Steers Shipped From France to Italy

Abstract: Bovine respiratory disease (BRD) is a complex, multifactorial syndrome and one of the major welfare and economical concerns for the cattle industry. This 1-year cross-sectional study was aimed at documenting the prevalence of BRD-related pathogens and clinical signs before and after a long journey and at identifying possible predisposition factors. Male Limousine beef steers (n = 169) traveling from France to Italy were health checked and sampled with Deep Nasopharyngeal Swabs (DNS) at loading (T0) and 4 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Transport-associated stress can alter immune functions, potentially compromising the animal's welfare by increasing the likelihood of infection and/or clinical disease. Among transport-related health problems, BVDV infections are common and can be severe [26][27][28]. A widespread route of spreading the virus is possible through the movement of PI cattle between herds [29,30], which is highly probable in herds in which the movement frequency is high [31].…”
Section: Discussionmentioning
confidence: 99%
“…Transport-associated stress can alter immune functions, potentially compromising the animal's welfare by increasing the likelihood of infection and/or clinical disease. Among transport-related health problems, BVDV infections are common and can be severe [26][27][28]. A widespread route of spreading the virus is possible through the movement of PI cattle between herds [29,30], which is highly probable in herds in which the movement frequency is high [31].…”
Section: Discussionmentioning
confidence: 99%
“…The reverse transcription using random hexamers and MuLV reverse transcriptase (GeneAmp ® RNA PCR, Applied Biosystems, Applera Italia, Monza, Italy) was performed in a total volume of 10 μL for the detection of BCoV, BVDV, BRSV and BPiV according to the manufacturer’s protocol. Then, the RT-qPCR for the detection of the above RNA viruses and of the DNA pathogens BAdV, BoHV-1, M. haemolytica , P. multocida , H. somni and M bovis was carried out using primers and TaqMan probe and the same reaction conditions and reaction mix components, as previously reported [ 7 , 8 , 10 ]. Briefly, 10 μL of cDNA or extracted DNA were added to 15 μL of the reaction master mix (IQ™ Supermix, Bio-Rad Laboratories Srl, Segrate, Italy) containing 0.6 μM of each primer and 0.4 μM probe.…”
Section: Methodsmentioning
confidence: 99%
“…Bovine coronavirus (BCoV) belongs to the Betacoronavirus genus, subgenus Embecovirus , and is responsible for different clinical diseases in ruminants affecting both respiratory and enteric tracts, such as neonatal diarrhea, the wintery disease in adults and respiratory diseases as a cofactor of the Bovine Respiratory Syndrome (BRD) [ 7 , 8 , 9 , 10 ]. Regardless of the clinical signs, BCoV, which is also commonly identified in healthy cattle [ 11 ], is shed both in the feces and in the nasal secretions.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential source to consider is the direct inhalation of air in different weather conditions as survivability of microorganisms in the air can be influenced by temperature, humidity, UV light, etc. [ 11 , 103 ]. These dynamic movements of microbiota are relevant for our understanding of pathogenesis in pulmonary health and disease [ 104 ].…”
Section: Biogeography Of the Bovine Respiratory Tract And Microbiotamentioning
confidence: 99%
“…Many studies have confirmed that the alteration of the respiratory microbiota can be observed in calves with clinical BRD. For example, the nasopharyngeal microbiota in BRD-affected feedlot calves was distinct from pen-matched healthy controls [ 22 , 103 ], a distinct longitudinal shift of microbial composition of the nasopharynx from feedlot arrival to when BRD was diagnosed was observed in another study [ 90 , 107 ], and bacterial families associated with BRD, including Mycoplasma and Pasteurellaceae , had greater abundances and frequencies in lung tissue samples from calves with BRD signs [ 52 ]. Although these reports support the hypothesis that microbial dysbiosis is associated with BRD, we still do not know the accuracy of the association between the microbiome and BRD despite the microbial changes found.…”
Section: Association Between the Respiratory Microbiome And Brdmentioning
confidence: 99%